Synthesis and SAR studies of 3, 6-disubstituted indazole derivatives as potent hepcidin production inhibitors. Issue 10 (15th May 2017) - Fukuda, Takeshi; Ueda, Kenjiro; Ishiyama, Takashi; Goto, Riki; Muramatsu, Sumie; Hashimoto, Masami; Watanabe, Kengo; Tanaka, Naoki
Graphical abstract: Abstract: Hepcidin has emerged as the central regulatory molecule of systemic iron homeostasis. Inhibition of hepcidin could be a strategy favorable to treating anemia of chronic disease (ACD). We report herein the synthesis and structure-activity relationships (SARs) of a series of indazole compounds as hepcidin production inhibitors. The optimization study of compound1 led to a potent hepcidin production inhibitor45, which showed serum hepcidin lowering effects in a mouse IL-6 induced acute inflammatory model.